Adoption or implementation: performance measurement in the city of Guangzhou's Department of Education. Issue 4 (1st October 2016) - Niu, Meili
Abstract: Performance-based budgeting (PBB) has become popular over recent decades in both developed and developing countries. How a line agency evaluates program performance is crucial to understand PBB reform in the Chinese budgeting system. This study uses the Education Department of a major Chinese city that pioneered PBB reform in China. Inspired by the conceptual framework developed by Julnes and Holzer (2001), the author finds that the Education Department 'adopted' the techniques of performance measurement at the beginning of the reform then moved to the 'implementation' stage shortly thereafter. Unfortunately, after three years of ambitious innovation, the department reverted back to the 'adoption' stage. Apart from the technical difficulties involved in the reform, other contextual factors—leadership changes, accountability mechanisms, lack of consensus on the approach reform should take, and organizational capacity—shaped the direction of the PBB reform.